A New Legal Framework for Online Platforms in the European Union (and Beyond) - Julián López Richart (Review of European and Comparative Law)
In the early 2000s, the EU adopted the Electronic Commerce Directive to regulate information society service providers. An important part of this piece of legislation was the safe harbor provisions, which exempted intermediary service providers from liability for illegal content transmitted or hosted by their users, provided that they complied with specific conditions. After more than twenty years, the emergence of significant online platforms and the increased use of those services has resulted in new risks and challenges for individuals, companies, and society as a whole, which led the European Union to adopt a new regulatory framework for intermediary services. The Digital Services Act retains the liability exemption regime of the Electronic Commerce Directive but introduces new transparency and due diligence obligations for intermediary services, especially for online platforms. The new regulatory framework is expected to substantially impact globally, as it applies to all intermediary service providers offering services within the EU, regardless of their location. This study explores the main features of the DSA and their potential effects on the future development of the Internet.